Magnetic Ligation Method for Quantitative Detection of MicroRNAs. Issue 7 (14th February 2014) - Liong, Monty; Im, Hyungsoon; Majmudar, Maulik D.; Aguirre, Aaron D.; Sebas, Matthew; Lee, Hakho; Weissleder, Ralph
<x xml:space="preserve">Abstract</x> A magnetic ligation method is utilized for the detection of microRNAs among a complex biological background without polymerase chain reaction or nucleotide modification. The sandwich probes assay can be adapted to analyze a panel of microRNAs associated with cardiovascular diseases in heart tissue samples. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>